Chromobox Homolog 8 (CBX8) in Human Tumor Carcinogenesis and Prognosis: A Pancancer Analysis Using Multiple Databases - Shi, Dongjie; Ao, Lei; Yu, Hua; Xia, Yongzhi; Li, Juan; Zhong, Wenjie; Xia, Haijian (Frontiers in Genetics, 2021)
Some emerging studies have suggested that CBX8 may play a critical role in carcinogenesis and prognosis in human cancer. Based on The Cancer Genome Atlas (TCGA)’s available data and the Gene Expression Omnibus (GEO) database, we conducted a systematic analysis of the carcinogenic effects of the CBX8 gene. We used TIMER2, GEPIA2, UALCAN, cBioPortal, Kaplan-Meier plotter, OncoLnc, STRING, HPA, and Oncomine data analysis websites and R data analysis software to analyze available data. The results show that the level of expression of CBX8 was significantly different among 27 different types of tumors and adjacent normal tissues. Moreover, we found that CBX8 expression had a close relationship with prognosis in some kinds of cancers. The phosphorylation level of some protein sites (such as S256) was significantly increased in tumors. CD8+ T-cell, B-cell and cancer-associated fibroblast infiltration levels were associated with CBX8 expression. The results of enrichment analysis indicated that the main biological activities of CBX8 are connected to gene transcription and repair of DNA damage. In conclusion, the level of expression of CBX8 was closely related to tumor carcinogenesis and prognosis, which needs further experimental verification.